How They Lived 2 : The Everyday Lives of Hungarian Jews, 1867-1940: Family, Religious, and Social Life, Learning, Military Life, Vacationing, Sports, Charity - Koerner, András (Book collections on Project MUSE., 2016)
Having presented the physical conditions among which Hungarian Jews lived in the late 19th and early 20th centuries--the kind of neighborhoods and apartments they lived in, and the places where they worked--this second volume addresses the spiritual aspects and the lighter sides of their life. We are shown how they were raised as children, how they spent their leisure time, and receive insights into their religious practices, too. The treatment is the same as in the first volume. There are many historical photographs at least one picture per page and the related text offers a virtual cross section of Hungarian society, a diverse group of the poor, the middle-class, and the wealthy. Regardless of whether they lived integrated within the majority society or in separate communities, whether they were assimilated Jews or Hasidim, they were an important and integral part of the nation. Through arduous work of archival research, Koerner reconstructs the many diverse lifestyles using fragmentary information and surviving photos.